ANALISIS KEBUTUHAN INFORMASI STANDAR DI KAWASAN PUSPIPTEK SERPONG: BERDASARKAN JENIS DAN KLASIFIKASINYA - Rahartri, Rahartri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2019)
This study aims to find out the standard information needs in the Puspiptek Region. While the specific objective of this study is to know the types of standard and standard classification required. The study was carried out descriptively. The data were collected by inventorying standard information needs during the 2011-2017 period. The results of this study concluded: 1) the type of standard information needed in Puspiptek Serpong Area are ASTM, JIS, ISO, BS, SNI, DIN, IEC, UIC; 2) based on the classification, the standards needed in the Puspiptek Serpong area are: a) ASTM, miscellaneous material classification; miscellaneous subjects; cementious, ceramic, concrete, and masonry material; b) JIS, railway engineering classification; chemical engineering; mechanical engineering; c) ISO, rubber and plastic industries classification; metallurgy; road vehicles engineering; d) British standard, agriculture classification; construction materials and building; chemical technology; e) SNI, metallurgy classification; food technology; construction materials and building; f) DIN standard, rubber and plastic industries classification; paint and colour industries; g) IEC standard, electrical engineering classification; testing/ environmental testing. The results of this study can be the recommendations for decision makers in the context of procurement/provision of documents, especially standard documents in the Puspiptek Serpong, for the development of science and technology.